2006
DOI: 10.1590/s1516-89132006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eugenol on growth and listeriolysin o production by Listeria monocytogenes

Abstract: The inhibitory effect of eugenol, a naturally occurring compound mainly present in the essential oil fraction of cloves, was studied on the growth and listeriolysin O (LLO) production by Listeria monocytogenes. Potassium efflux from cells promoted by eugenol was also determined after 24 h incubation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 19 publications
(25 reference statements)
1
19
1
1
Order By: Relevance
“…This finding is consistent with previous studies demonstrating that honokiol possesses good antimicrobial activity (Ho et al, 2001;Hu et al, 2011). The anti-L. monocytogenes activity of honokiol, with a lower MIC value, was stronger than other naturally occurring compounds, such as the essential oils eugenol (Filgueiras & Vanetti, 2006), bay, cinnamon, clove, thyme (Fazlara et al, 2008;Smith-Palmer et al, 1998) and rosemary (Pandit & Shelef, 1994).…”
Section: Honokiol Represses the Transcription Of Genes Encoding Llo Asupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with previous studies demonstrating that honokiol possesses good antimicrobial activity (Ho et al, 2001;Hu et al, 2011). The anti-L. monocytogenes activity of honokiol, with a lower MIC value, was stronger than other naturally occurring compounds, such as the essential oils eugenol (Filgueiras & Vanetti, 2006), bay, cinnamon, clove, thyme (Fazlara et al, 2008;Smith-Palmer et al, 1998) and rosemary (Pandit & Shelef, 1994).…”
Section: Honokiol Represses the Transcription Of Genes Encoding Llo Asupporting
confidence: 92%
“…Compared with previous studies, our results indicate that the honokiol was more effective in inhibiting LLO secretion than eugenol (Filgueiras & Vanetti, 2006), sorbate and NaCl (McKellar, 1993). The major extracellular protein (p60) produced by L. monocytogenes, which acts as a murein hydrolase required in the last step of cell division, was also analysed.…”
Section: Honokiol Represses the Transcription Of Genes Encoding Llo Amentioning
confidence: 53%
See 1 more Smart Citation
“…Specific effects on bacterial virulence factors, that is the products by which bacteria establish infection and produce disease, have also been identified. Examples include that cinnamaldehyde interferes with quorum sensing communication processes mediated by two different types of signalling compounds, acyl homoserine lactones and a group known collectively as autoinducer-2 (AI-2) [197,198]; Ocimum gratissimum essential oil inhibits extracellular protease activity and cell-wall lipopolysaccharide expression [199]; eugenol inhibits listeriolysin O production [200]; and mint (Mentha piperita) essential oil reduces levels of staphylococcal enterotoxin B [201]. In fungi too, specific effects have been identified that compromise cell integrity [202], viability or virulence [203,204].…”
Section: Mechanisms Of Antibacterial and Antifungal Actionmentioning
confidence: 99%
“…In Malaysia, clove is locally known as bunga cengkih, which is popularly used in aromatherapy products and as a flavour enhancer in many dishes. Eugenol has been proven effective in combating several pathogens such as Salmonella typhi, Proteus mirabilis (Devi et al 2010(Devi et al , 2013, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa (Walsh et al 2003) and Listeria monocytogenes (Filgueiras & Vanetti 2006). It is also traditionally used as an instant remedy for toothache.…”
Section: Introductionmentioning
confidence: 99%